The adverse effects of the respiratory effort on the pulmonary circulation are independent of the ejection fraction and heart failure etiology. (3rd October 2022) - Markovitch, N; Rispler, S; Feld, Y; Solomonica, A; Yalonetsky, S; Musallamis, A; Kerner, A; Roguin, A; Landesberg, A
Abstract: Introduction: Heart failure (HF) is associated with hemodynamic lung congestion that leads to dyspnea and excessive respiratory effort. Purpose: We hypothesized that this HF induced excessive respiratory effort adversely affects both ventricles loading conditions, leading to a vicious cardiopulmonary cycle and progressive cardiac deterioration, and that this vicious cardiopulmonary cycle is independent of HF etiology. Methods: The hemodynamic and respiratory indices were simultaneously measured in patients undergoing right heart catheterization for the diagnosis of dyspnea. The pulmonary wedge pressure (PCWP) is modulated by the changes in the intrathoracic pressure. The latter is determined by the respiratory effort. To quantify the respiratory effort, the PCWP was decomposed into cardiac and respiratory waves. The respiratory effort (Presp) was defined as the peak to peak amplitude of the respiratory wave that modulated the PCWP. The immediate effects of the respiratory effort on the pulmonary capillary wedge pressures (PCWP) were scrutinized by asking the patients to perform intentional vigorous breathing and short apneic events. Results: The HF patients (N=50) exhibited a high Presp of 9.3±5.0 mmHg, ∼3.5-fold higher than the normal respiratory effort. The baseline end-expiratory PCWP (PCWPee) and end-expiratory pulmonary artery pressure of the HF patients have linear relationship with the baseline Presp with slops of 0.78±0.05 and 1.42±0.09 respectively. The changes in PCWPee appeared immediately, within a single breathing-cycle (t =1.65±0.39 sec) in all patients, when each patient intentionally changed the respiratory effort from apnea to his maximum Presp of 19.8±8.6 mmHg. The PCWP during apnea underestimated the HF severity and yielded lower PCWPee while severe respiratory effort markedly increased the PCWPee. Interestingly, similar slope of the instantaneous relationship between the varying Presp and observed PCWPee was obtained for all the patients, independently of the baseline PCWPee-. The PCWPee rose immediately by 0.43±0.15 for every 1 mmHg of Presp. Similar slope was observed in HF patients with ischemic (N=24) and non-ischemic (N=26, p=0.36) HF diseases (p=0.26), and in those with preserved (N=35) or reduced (N=15) ejection fractions (p=0.91). Conclusions: The respiratory effort has immediate effects on the hemodynamic congestion and the workloads of the heart, and this adverse effects are independent of HF etiology. The observations support the existence of a vicious cardiopulmonary cycle that can lead to decompensation, where the respiratory effort plays a pivotal role. It may explain the similar prognosis of patients with various ejection fractions and etiologies, but with similar dyspnea severity and clinical symptoms. Funding Acknowledgement: Type of funding sources: None.